Jordanian banking system: Analysis of technical efficiency and performance - Mohammad W. Alomari; Ala' Bashayreh; Samer Abdelhadi (Financial Studies, 2020)
The purpose of this study is to examine the connection between technical efficiency and banks' performance for 13 commercial banks in Jordan over the period 2010-2017. For this purpose, this study will employ the nonparametric model using the linear programming by Data Envelopment Analysis (DEA) to calculate technical efficiency and the panel regression analysis to estimate the relationship between technical efficiency and Banks' performance measured by return on asset (ROA), return on equity (ROE)and Tobin's Q. The empirical findings reveal that pure technical efficiency (PTE)is statistically significant with positive effect on ROA, ROE and Tobin's Q. Further, the relative technical efficiency (RTE) or scale efficiency (SE) has positive significant impact on ROA, ROE, and Tobin's Q. The market share and the ATMs coverage sharealso has a positive effect on bank's performance.On the other hand, bank's size has no significant effect on ROA and ROE but weak positive effect on Tobin's Q.
Keywords: G14; G21; L25; 330; echnical Efficiency; Banks' Performance; Commercial Banks; Data Envelopment Analysis